Uterine torsion in twin pregnancy with complete bicorporeal uterus, double cervix, longitudinal non-obstructing vaginal septum - a case report - Gao, Qianqian; Xiong, Jinqiu; Zhu, Yuchun (Frontiers in Surgery, 2023)
Uterine torsion is a rare obstetric complication in humans, but has been reported in association with severe complications,such as placental abruption, uterine rupture, fetal bradycardia or death .We present a case of uterine torsion diagnosed at emergency cesarean delivery with prolonged fetal bradycardia after suspected diagnosis of placental abruption.Obstetricians should be aware of the possibility of uterine torsion as a complication of pregnancy to avoid a delayed diagnosis of uterine torsion.